An investigation of the knowledge level of the primary school first level managers, school guidance teachers, and class teachers about their own and each other's guidance duties - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
The aim of this study is investigating of the knowledge level of the primary school managers, guidance teachers and class teachers about their own and each others guidance duties. The sample of this research is composed by 72 managers, 59 guidance teachers and 317 class teachers which have been selected by random set sampling method from 46 state primary schools and 11 private primary schools. The Guidance Duty Knowledge Scale, which has been developed by the researchers has been used to get data. As a result of the research it has been found that the knowledge about their own guidance duties of the school managers, guidance teachers, and class teachers was at medium level. Also, it has been found that the knowledge level about their each other's' guidance duties of the samples was more higher than the knowledge level of their own guidance duties. (C) 2013 The Authors. Published by Elsevier Ltd.
Keywords: Words: Primary school first level manager; class teacher; school guidance teacher; guidance duties